Identifying the need to institutionalize digital equity among faculty: the experience of the Kenya Medical Training College - Gicheru, Wagaki; Mwangi, Nyawira (Frontiers in Education, 2023)
The use of digital tools and applications in health professions education is increasing exponentially, however this has the potential to increase the digital inequities with the resulting effect of vulnerable groups facing an increased risk of digital exclusion. It is therefore important to approach digitalization with contextual determinants of the intended and unintended impact in mind. We present a perspective paper on digital equity, informed by lessons learnt at the Kenya Medical Training College (KMTC).Using a case description methodology, we examined routine educational data collected from faculty at KMTC in November 2022. This included quantitative and qualitative data on access, ownership, utilization, confidence and skills to create, share, and exchange knowledge on the institution's learning management system. We used these factors as the conceptual framework for understanding how faculty adopt digitalization in health professions education.306 faculty responded to the survey (response rate 27.8%) of whom 90.8% and 75.2% had personal laptops at home and at work and 75.9% had internet at work. 53.4% (n-163) knew they had accounts created on the institution's learning management system (LMS) majority of whom had basic skills and were able to perform skills such as logging in and accessing learning resources. However, a minority had advanced skills needed for teaching and learning in the LMS.Medical education Institutions in LMICs need to adopt programs to enhance digital literacy and monitoring of access, utilization and self-efficacy across all learner and faculty groups, to ensure that digital technologies reduce rather than exacerbate existing inequities.